Electrospun flexible lignin/polyacrylonitrile-based carbon nanofiber and its application in electrode materials for supercapacitors. Issue 3 (February 2022) - Wu, Hong; Liu, Chengkun; Jiang, Zhiwei; Yang, Zhi; Mao, Xue; Wei, Liang; Sun, Runjun
In this study, a lignin/polyacrylonitrile (PAN) composite nanofiber membrane is prepared by electrospinning and used as the precursor to prepare flexible carbon nanofibers (CNFs) through pre-oxidation and carbonization. The micromorphology, crystal structure, pore size distribution and specific surface area of the CNFs are characterized by field emission scanning electron microscopy, X-ray diffraction, Raman spectroscopy and specific surface adsorption analysis, respectively. The electrochemical properties of the CNF membrane are also investigated by cyclic voltammetry, galvanostatic charge–discharge and electrochemical impedance spectroscopy due to its potential application in binder-free electrode materials for supercapacitors. We successfully prepared flexible CNFs with an average diameter of about 539 nm and a specific surface area of 1053.78 m 2 /g when the mass ratio of lignin to PAN was 9:1 in a solution concentration of 28 wt%. The CNFs are loaded onto nickel foam to prepare the electrode materials for supercapacitors without a binder. When the current density is 0.5 A/g, the specific capacitance could be up to 201.27 F/g and the equivalent series resistance is only 0.57 Ω, which shows an excellent electrochemical performance. This study not only provides a theoretical basis for the high-value utilization of lignin and the preparation of flexible lignin/PAN-based CNFs, but also provides a new type of environmentally friendly raw material for the electrodes of supercapacitors and could be helpful to alleviate the energy crisis and environmental pollution.